Genetic Variation of Vanda foetida J. J. Sm. ; a Rare and Endemic Orchid in South Sumatra Based on RAPD Analysis - Rindyastuti, Ridesti; Metusala, Destario; Kumalawati, Dian Aruni; Daryono, Budi Setiadi (Journal of Tropical Biology & Conservation (JTBC), 2023)
Vanda foetida J.J.Sm., which is an endemic orchid species in Sumatra has taxonomically disappeared for over 100 years since it was described in 1906. The distribution of V. foetida was limited due to over-exploitation of this orchid and changes to land-use. The study of genetic variation of V. foetida in its natural habitat, Mount Dempo and Padiampe, South Sumatra was conducted based on Random Amplified Polymorphic DNA (RAPD) analysis for genetic variation using 8 primers (OPU 3, OPU 5, OPU 6, OPU 7, OPU 12, OPU 13, OPU 14 and OPU 16). Genetic variation in each population was detected by h value (Nei’s genetic diversity) which was 0.1999 and 0.1778 for Mount Dempo and Padiampe, respectively. This value was higher compared to those of other rare orchid species even though it only has a small population. V. foetida originated from two populations forming two main clusters in dendrogram with 67 % (0.67) degree of similarity. The dendrogram indicated that the two populations are connected, and assumed as one large population in the past and were separated from larger population by habitat fragmentation. This species was not genetically in danger and will be able to survive if its natural habitats are remained.